Armatophallus gen. n., a new genus of gelechiid moths (Lepidoptera, Gelechiidae) from the Afrotropical and Oriental regions - Bidzilya, Oleksiy V. (Zootaxa, 2015)
Armatophallus, gen. n., is established for six species: A. exoenota (Meyrick, 1918), comb. n. (ex Gelechia) (= Gelechia xylophaea Meyrick, 1921, syn. n.); A. crudescens (Meyrick, 1920), comb. n. (ex Gelechia); A. kuehnei, sp. n. (Rwanda); A. akagericus, sp. n. (Rwanda); A. hackeri, sp. n. (Yemen, Ethiopia); and A. indicus, sp. n. (India). The systematic position of the new genus is briefly discussed. A key to the species is given based on external characters and the genitalia of both sexes. Adults and genitalia of all species are illustrated.